Short-term outcomes of non-ST segment elevation acute coronary syndrome after percutaneous coronary intervention: a single-center speckle tracking echocardiographic study in Vietnam - Trinh, Ha Viet; Nguyen, Dung Viet; Do, Loi Doan; Le, Binh Thanh; Nguyen, Hoai Thi Thu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundData on the prognostic value of myocardial strain in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) from low- and middle-income countries remain scarce. This study aimed to evaluate the prognostic significance of left ventricular myocardial strain in patients with NSTE-ACS after successful percutaneous coronary intervention (PCI) in Vietnam.MethodsIn this prospective cohort study, consecutive patients diagnosed with NSTE-ACS and treated with PCI underwent conventional and speckle-tracking echocardiography within 24 h post-PCI to assess myocardial function, including global longitudinal strain (GLS), global circumferential strain (GCS), and global radial strain (GRS). Patients were followed for 12 months. The association between echocardiographic parameters and major adverse cardiovascular events (MACE) was analyzed using Kaplan–Meier survival curves and Cox proportional hazards models. Prognostic performance was assessed using receiver operating characteristic (ROC) curves, area under the curve (AUC), and other diagnostic indices.ResultsA total of 127 patients were included (mean age 65.5 ± 10.5 years; 71.3% male). During 12 months of follow-up, 26 patients (20.5%) experienced MACE. The MACE group had significantly impaired GLS, GCS, and GRS compared with the event-free group (all p < 0.0001). In multivariable analysis, only higher (less negative) GLS remained an independent predictor of MACE (HR: 1.62; 95% CI: 1.26–2.08; p < 0.001). GLS demonstrated the strongest prognostic performance among echocardiographic variables, with an AUC of 0.967 (95% CI: 0.941–0.994). At the optimal cutoff, an GLS ≥ –16% demonstrated a sensitivity of 100% (95% CI: 86.8–100) and a specificity of 85.1% (95% CI: 76.7–91.4).ConclusionIn patients with NSTE-ACS, post-PCI GLS, GCS, and GRS were significantly more impaired in those who developed MACE compared with the event-free group, indicating underlying cardiac dysfunction or myocardial injury. Among these parameters, GLS emerged as an independent predictor of MACE after PCI and may serve as a valuable tool for identifying high-risk patients.